Memory Recall After “Learning by Doing” and “Learning by Viewing”: Boundary Conditions of an Enactment Benefit - Steffens, Melanie C.; von Stülpnagel, Rul; Schult, Janette C. (Frontiers in Psychology, 2015)
According to common sense, things one has done are remembered better than things done by others that one has observed. On first sight, findings concerning memory for actions appear in line with that preconception: Performed actions (“subject-performed tasks”) appear to be remembered particularly well, and better than observed actions (“experimenter-performed tasks”). A closer look, however, reveals important exceptions regarding this enactment effect. The aim of the present paper is critically evaluating the literature that compares memory for performed and observed tasks. In recognition memory, an enactment effect has regularly been observed. In free recall, however, findings depended on the experimental design: When performed and observed actions were intermixed, an enactment effect was typically found. In contrast, in designs where actions were either all performed or all observed, this was rarely the case. We discuss underlying memory processes, potential moderator variables, open questions, and implications.